2023
DOI: 10.1111/jpn.13824
|View full text |Cite
|
Sign up to set email alerts
|

Diet supplemented with Saccharomyces cerevisiae from different fermentation media modulates the faecal microbiota and the intestinal fermentative products in dogs

Abstract: This study aimed at evaluating the coefficients of total tract apparent digestibility (CTTAD) of nutrients, metabolisable energy (ME), diet palatability, faecal fermentative products and microbiota of dogs fed yeasts from different fermentation media and its fractions. Four diets were evaluated: control, without yeast (CO); diet with 10 g/kg brewer's yeast (BY); diet with 10 g/kg brewer's yeast + corn yeast (BCY); and diet with 10 g/kg BCY + cell wall fractions (BCYF). Twelve adult dogs were distributed in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…A diet based on wet crude olive cake in Iberian pigs resulted in a better growth performance compared with dry olive pulp (91), and the addition of olive cake in finishing pig diets also increased FI and BWG (37). Similarly, Joven et al (75) reported in pigs an higher consumption of feeds and higher growth rates after a dietary supplementation with 5% or 10% of olive cake (replacing an equivalent proportion of barley in the diet) (Table 2). In contrast, during the pig finishing period, dietary supplementation with 100 mg/kg of partially defatted olive cake had no effect on growth performances, showed only a tendency to increase FCR (p = 0.059) and significantly reduced loin depth (32).…”
Section: Olive Pomace and Olive Cakementioning
confidence: 80%
See 4 more Smart Citations
“…A diet based on wet crude olive cake in Iberian pigs resulted in a better growth performance compared with dry olive pulp (91), and the addition of olive cake in finishing pig diets also increased FI and BWG (37). Similarly, Joven et al (75) reported in pigs an higher consumption of feeds and higher growth rates after a dietary supplementation with 5% or 10% of olive cake (replacing an equivalent proportion of barley in the diet) (Table 2). In contrast, during the pig finishing period, dietary supplementation with 100 mg/kg of partially defatted olive cake had no effect on growth performances, showed only a tendency to increase FCR (p = 0.059) and significantly reduced loin depth (32).…”
Section: Olive Pomace and Olive Cakementioning
confidence: 80%
“…Unaltered fecal concentrations of SCFA have been reported when yeast or yeast by-products were used (24,74,81,95,97). However, decreases in isovalerate and/or increases in propionate, butyrate, acetate and total SCFA when using yeast products have been reported by different authors (5,75,81,95). Van den Abbeele et al ( 85) also observed increases in acetate, butyrate and propionate when adding YCW in their in vitro experiment simulating the canine gut.…”
Section: -63 Daysmentioning
confidence: 95%
See 3 more Smart Citations